ANALISIS KARAKTERISTIK KONSUMEN PRODUK OLAHAN MANGGA DITINJAU DARI ASPEK DEMOGRAFIS, GEOGRAFIS, PSIKOGRAFIS SERTA PERILAKU KONSUMEN SEBELUM DAN SAAT PANDEMI COVID-19 - Elly Rasmikayati; Yuniar Dianti Fauziah; Lucyana Trimo; Rani Andriani Budi Kusumo; Bobby Rachmat Saefudin (Universitas Galuh Ciamis, 2021)
Recognizing the varied characteristics of consumers in consuming products, producers better understand the characteristics of their consumers in advance from various aspects in order to get maximum profit. Especially with the Covid-19 pandemic, it is expected to affect changes in many aspects. The purpose of this study is to identify how the characteristics of consumers of processed mango products are based on 4 aspects, namely geographic, demographic, psychographic and consumer behavior before and during the covid-19 pandemic. The research design used is a quantitative design with data analysis techniques used are descriptive analysis, crosstabulation analysis. This research was conducted at the Faculty of Agricultural Industrial Technology, University of Padjadjaran with a sample determined using the simple random sampling method of 120 people. The results showed: (1) The characteristics of consumers before the covid-19 pandemic were dominated by female sex with the age of 20 years, the average pocket money earned was Rp. 500,001 – 2,500,000 and the average expenditure was Rp. 0 – 1,000. .000, has a residence in West Java and the type of processed product that is most often consumed is juice with a consumption rate of 1x per month; (2) During the covid-19 pandemic, the level of consumption of processed mango products that have a health effect has increased, while the consumption of processed mango products that are snacks will decrease because the pocket money that student get is reduced. Then the location for purchasing processed mango products will shift from modern retail to online stores.